Analisis Learning Obstacle pada Materi Fungsi Kuadrat: Studi Fenomenologi Siswa - Azizah, Haura Nur; Maudy, Septiani Yugni; Mulia Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to identify and describe the learning obstacles experienced by 11th-grade students in understanding the concept of quadratic functions. The research method used in this study was phenomenology, involving 25 students at SMAN 1 Serang Baru, from whom 3 students were purposively selected as representatives. The results of the study indicate that students experience three types of learning obstacles: ontogenetic obstacles in the form of gaps in understanding prerequisite material; didactic obstacles in the form of a tendency to follow learning procedures without comprehending the concepts thoroughly; and epistemological obstacles in the form of errors in understanding quadratic equations, discriminants, and the graphical representation of parabolas. The conclusion of this study highlights the importance of instructional designs that address students’ needs, strengthen conceptual understanding, bridge prerequisite material with new material, and build students’ self-confidence throughout the learning process. Keywords: Didactical Obstacle; Epistemological Obstacle; Learning Obstacle; Ontogenic Obstacle; Quadratic Function